A Phase 1 Proof of Concept Study Evaluating the Addition of an LSD1 Inhibitor to Nab-Paclitaxel in Advanced or Metastatic Breast Cancer (EPI-PRIMED) - Prasanna, Thiru; Malik, Laeeq; McCuaig, Robert D.; Tu, Wen Juan; Wu, Fan; Lim, Pek Siew; Tan, Abel H. Y.; Dahlstrom, Jane E.; Clingan, Philip; Moylan, Eugene; Chrisp, Jeremy; Fuller, David; et al. (Frontiers in Oncology, 2022)
Objective Lysine-Specific Demethylase-1 (LSD1) is overexpressed in breast cancer cells and facilitate mesenchymal properties which may contribute to therapeutic resistance and cancer progression. The purpose of this study was to investigate the safety of combination, nab-paclitaxel and phenelzine, an irreversible LSD1 inhibitor in patients with metastatic breast cancer (mBC). Methods Eligible patients with mBC were treated with nab-paclitaxel (100mg/m2) weekly for 3 weeks with one week break in a 28-day cycle. Dose escalation of phenelzine followed the Cumulative Cohort Design and phenelzine treatment commenced from day 2 of first cycle. Eleven patients were screened, and eligible patients were enrolled in cohorts with the dose of phenelzine ranging from 45mg to 90mg. Results The Optimum Biological Dose was established at 60mg of phenelzine daily in combination with nab-paclitaxel and considered as the recommended phase 2 dose. Most (95%) of adverse events were grade 1 or 2 with two grade 3 events being diarrhea and neutropenia at 45mg and 60mg phenelzine respectively, with no unexpected toxicity/deaths. Commonly reported toxicities were fatigue (n=4,50%), dizziness (n=6, 75%), neutropenia (n=3,37.5%), peripheral neuropathy (n=3,37.5%), diarrhea (n=2,25%), and hallucination (n=2,25%). After a median follow up of 113 weeks, all patients showed disease progression on trial with 4 patients being alive at the time of data cut off, including one patient with triple negative breast cancer. Median progression-free survival was 34 weeks. Significant inhibition of LSD1 and suppression of mesenchymal markers in circulating tumor cells were noted. Conclusion Phenelzine in combination with nab-paclitaxel was well tolerated, without any unexpected toxicities in patients with mBC and demonstrated evidence of antitumor activity. For the first time, this proof-of-concept study showed in-vivo inhibition of LSD1 suppressed mesenchymal markers, which are known to facilitate generation of cancer stem cells with metastatic potential.